Glutathione reductase plays a role in the metabolism of methylmercury degradation in Rhodotorula mucilaginosa - Yi Guo; Wenlong Deng; Qigui Mo; You Yu; Zhenwang Zhang; Mingjie Wei; Ruiling Tang; Surui Lu; Yanting Su (Microbiology Spectrum)
ABSTRACT Mercury pollution is a kind of heavy metal pollution with great harm and strong toxicity which exists worldwide. Some microorganisms can convert highly toxic methylmercury into inorganic mercury compounds with significantly reduced toxicity. This is an effective means of methylmercury pollution remediation. As a safe microorganism with great potential in the remediation of heavy metal pollution, Rhodotorula mucilaginosa has not been studied in the remediation of methylmercury. Here, a R. mucilaginosa strain Rm4 with high methylmercury resistance was obtained by wild-strain screening. Its minimal inhibitory concentration and minimum lethal concentration reached 3 and 6 mg/L, respectively. At the same time, Rm4 can also degrade methylmercury. Unlike the traditional microbial methylmercury degradation pathways, R. mucilaginosa’s genome does not encode the organomercury lyase gene MerB. However, transcriptomic analysis revealed that the glutathione reductase of R. mucilaginosa responds to the methylmercury degradation process. Structural domain analysis and molecular docking experiments suggest that the glutathione reductase of R. mucilaginosa has the potential to directly or indirectly participate in methylmercury degradation metabolism. Metabolic indicator tests of engineered strains overexpressing the glutathione reductase encoding gene also support this notion.IMPORTANCEThe remediation of methylmercury pollution is crucial for environmental health. The ability of Rhodotorula mucilaginosa to resist and degrade methylmercury offers a new avenue for bioremediation efforts. Understanding the metabolic pathways involved, particularly the role of glutathione reductase, enhances our knowledge of how Rhodotorula mucilaginosa responds to methylmercury and opens up new possibilities for future research in bioremediation strategies.